(untitled) (Indian Journal of Arid Horticulture, 2018)
Karonda is an important crop indigenous to India which is used in alternative medicine, health foods and herbal products. It has good potential in processed forms but little information is available on changes of nutritional quality of different karonda processed products during storage. Therefore, the present investigation was carried out to study the changes of nutritional quality of different karonda processed products during storage. Four products were made from karonda viz., jelly, jam, candy and squash, stored for 120 days and analyzed biochemically. The four months storage study revealed that across all the products the total soluble solids, acidity, reducing sugar, total sugar and browning was found to increased significantly from the initial mean values of 67.5 Brix, 0.35%, 25.9%, 61.7% and 0.38 O.D. of fresh products to the final value of 74.2 Brix, 2.11%, 31.8%, 63.3% and 0.44 O.D. at the end of storage, respectively. While, the non reducing sugar, ascorbic acid, moisture content and anthocyanin content of various karonda products were decreased significantly from the initial mean values of 33.6%, 3.53 mg/100g, 4.86%, and 2.39 mg/100g of fresh products to the final value of 29.4%, 1.76 mg/100g, 1.83%, and 0.99 mg/100g at the end of storage, respectively. Across all the products, an increasing trend in bacterial and fungal count was recorded up to 120 days of storage as compared to fresh products. Minimum bacterial (1.84 x 10 cfu/g) and fungal count (2.09 x 10 cfu/g) was obtained in fresh products and it was